Modified PEHPS medium as an alternative for the in vitroCulture of Giardia lamblia - Vargas Villarreal, Javier; Mata Cárdenas, Benito David; Hernández García, Magda Elizabeth; Garza González, Jesús Norberto; De la Garza Salinas, Laura Hermila; González Salazar, Francisco (2014)
Commercial culture media present interlot variations in biological activity.We have previously designed a homemade and economic culture medium, PEHPS medium, for the axenic cultivation of Entamoeba histolytica and Trichomonas vaginalis. Trophozoites of amoebae and trichomonads grow well in this medium. Furthermore, the medium is stable for several months when stored frozen or refrigerated. The objective of this work was to modify PEHPS medium to support the in vitro growth of Giardia lamblia. Inocula of 5 × 103 trophozoites/mL of G. lamblia were incubated at 36.5∘ C in modified PEHPS or TYI-S-33 medium. Then, the growths of the three Giardia strains in both media were compared. The logarithmic growth phase lasted 72 h; the mean yield of the strains ranged from 10.06 to 11.43 × 105 Giardia trophozoites/mL, and the range of duplication time in the three strains was from 5.67 to 6.06 in modified PEHPS medium. These growth characteristics were not significantly different from those obtained with TYI-S-33 medium. We conclude that modified PEHPS medium might be used for the axenic cultivation of G. lamblia.